PERLINDUNGAN HUKUM HASIL KEKAYAAN ALAM TALAS BOGOR DALAM PERSPEKTIF HAK KEKAYAAN INTELEKTUAL - Abdul Karim; Efridani Lubis (JURNAL ILMIAH LIVING LAW, 2016)
Geographical indication protection is an important trademark system in Indonesia, as an archipelogic state with its rich knowledge, tradition, culture and tropical climate which produces various economic potencial product. Indonesia should have adequate system of geographical indication protection, its protect the environment and maximizing human and natural resources. This research avestion are legal protection of intellectual property right of Bogor taro and lapis talas sangkuriang. Method used in this research is normative juridical approach that is conceptualized law as norms, rules, principle or dogmas. This research use literature study. In this case the literature material is primary data under study which is categorized into secondary data. The results of this research are 1) Taro Bogor need to get legal protection through Geographical Indication of both active stelsel and passive stelsel; 2) Lapis Talas Sangkuriang Bogor can only get legal protection after it is registered, since Geographical Indication is a constitutive system, namely registration is the main requirement to get protection.